Comparative study of ameliorative effect of ethanolic And aqueous extract of callus of oroxylum indicum [l.] Vent. On tobacco extract induced Damage in human lymphocytes - MAMTA GOKHALE; ASHA KHANNA; DAYASHANKAR GAUTAM (International Journal of Pharma and Bio Sciences, 2017)
Oroxylum indicum was analysed for its ameliorative effects as callus is known as a reservoir of metabolites of that plant from which it is developed.This study was conducted to study the ameliorative effect of ethanolic and aqueous extract of callus of Oroxylum indicum [L.] Vent. on tobacco extract induced cell damage in human peripheral blood lymphocytes (PBL). The cytotoxicity of tobacco extract on human PBL was tested at two hours exposure then aqueous (crude and 50%) and 70% ethanol (crude and 50%) extracts of callus were used to assess their ameliorative effects by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay.Aqueous and 70% ethanol extract of all types of callus were analysed for fresh weight, dry weight, presence of TPC (total phenol content), TFC (total flavonoid content) and antioxidant activity by 2, 2-diphenyl- 2- picrylhydrazyl (DPPH) method. Both extracts have been chemically analysed by GC-MS to observe the occurrence and area % of different compounds present. Isolated human lymphocyte cells were treated with TE for two hrs followed by cell viability test by MTT assay in an ELISA microplate reader and absorbance was read at 600 nm. After treatment with various callus extracts for 24 Hours (hrs.), the viability of lymphocytes was analysed. ‘t test’ was used for statistical analysis. It was observed that cell viability was significantly enhanced when TE injured cells were treated with 70% ethanol (crude and 50%) extract as compared to aqueous extract. However crude i.e., 70% ethanol extract showed better results. GC-MS chromatogram showed presence of flavonoid baicalein in 70% ethanol extract only.Survival rate of damaged lymphocytes might have been enhanced after callus extract treatment due to the presence of flavonoid baicalein in 70% ethanol extract.